The Application Of Law On The Criminal Law Of Incest Offices Reviewing From Bali Candidate Criminal Law - Hana Faridah (IHSA Institute, 2022)
Law has two forms, namely written and unwritten, one of the laws that has an unwritten form is customary law. As written law, the existence of customary law also plays a role in realizing an orderly and safe life, because in life there will always be actions that are not in accordance with applicable norms. Acts that are not in accordance with these norms are sometimes found to be in two legal domains or intersect with two legal domains. For example, between the realm of criminal law and the realm of customary law. Customary law has a strong influence in several areas in Indonesia, one of which is in the province of Bali, where most of the customary offenses are regulated in the rules (awig awig) of the village concerned. The attachment of religion, especially Hinduism to customary law in Bali, can be found in the way the Balinese people resolve a violation of their customs. One of the customary offenses regulated in the awig awig of the Balinese village is related to morality (the traditional offense of Gamia Gamana). This study uses empirical legal research methods that use primary data sources and secondary data sources that are descriptive with qualitative data analysis. The results of the analysis will be presented in a descriptive way, which describes the problems studied systematically and critically. Gamia Gamana is a violation of adat in the form of a prohibition on sexual relations between people who still have close family relationships (such as children and stepmothers, fathers and daughters, and so on). To restore the balance that has been disturbed as a result of unusual acts.